Indonesia's Presidential Threshold As Open Legal Policy In Election: As A Base For Muslim Studies - Anggar Putra (Jurnal Al Tasyri'iyyah, 2021)
Since its inception in the 2004 general election until the simultaneous general election in 2019, the use of standardization of presidential and vice presidential nominations, also known as the presidential threshold system, has garnered numerous benefits and drawbacks. Thus far, the writers have established that the presidential threshold system is an open legal policy (open legal policy) that does not violate the Republic of Indonesia's constitution or is constitutional. The purpose of this article is to examine the presidential threshold's compliance with an open legal policy from the standpoint of Islamic law. The research employs a legal-normative as well as a theological or syar'i approach. The study's findings indicate that the presidential threshold was established in conformity with open legal policy principles strengthened by Constitutional Court Decision 14/PUU-XI/2013. The presidential threshold system is one of the measures to strengthen the presidential system and simplify political parties, thereby enhancing long-term governance and promoting the legislative and executive institutions' professionalism in their performance. According to siyasa syariyyah, one must be a descendant of the Quraysh tribe in order to apply as a state or imamate leader. However, this requirement is not absolute; if one has been permitted to become a leader, one does not have to be a descendant of the Quraysh tribe in order to eliminate the sense of ashabiyah. Meanwhile, the presidential threshold system ensures full uniformity in order to allow for the nomination of candidates for state leaders (president and vice president). Keywords: Open Legal Policy; Presidential Thresholds; General election